Pengintegrasian Peer Assessment pada Model Direct Instruction untuk Meningkatkan Keterampilan Servis Backhand - Adawiyah, Siti Rabiatul (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aims to improve backhand serve technique skills through the implementation of peer assessment within a direct instruction model. This Classroom Action Research (CAR) was conducted over two cycles in class XI IPA MA An-Najah, Al-Halimy Sesela Islamic Boarding School, West Lombok Regency, involving 22 students. The instruments used included an observation sheet for lesson plan implementation and a peer assessment sheet. Data were analyzed descriptively and qualitatively using percentage analysis. The results showed that lesson plan implementation increased from 95% (cycle I) to 100% (cycle II), and classical mastery of backhand serve skills increased from 55% to 95%. These findings indicate that integrating peer assessment within the direct instruction model is effective in improving students' backhand serve technique skills. This research contributes to collaborative and reflective physical education learning strategies.